Sistem Pendukung Keputusan Penentuan Teknisi Terbaik PT Sapta Karya Manunggal Menggunakan Metode Topsis Berbasis Website - Arista, Theo Shandy; Novita, Dien (MDP Student Conference, 2024)
Information technology has now become a necessity that must exist in an organization because of the growing digital era and intense business competition, organizations must adapt to existing technological developments. The company has difficulties in processing the assessment and ranking of technicians because they have to record many technicians manually. The purpose of the system development is to create a dynamic decision system for determining the best technician according to company criteria using the TOPSIS method. The TOPSIS method is a multi-criteria decision-making method that can combine the weights of important criteria and has a unique principle where the chosen alternative must have the shortest distance from the positive ideal solution and the longest distance from the negative ideal solution. The decision support system is made transparent because the results of the calculations can be seen after the assessment process is carried out according to the standards and weights imposed by the company and the decision system made makes it easier for HRD to input data according to each technician. Based on the application that has been made regarding the decision support system for determining the best technician PT Sapta Karya Manunggal uses the topsis method based on a website, the suggestion from this paper is to try using other methods to make better decisions as a comparison.